Wellness Tourism in the Post-Pandemic Era: A PRISMA-Based Systematic Literature Review - Yadav, Monika; Gusain, Amit (PALASH A JOURNAL OF HOSPITALITY AND TOURISM SERVICE MANAGMENT, 2026)
The COVID-19 pandemic has significantly transformed global tourism patterns, leading to an increased emphasis on health, well-being, and sustainable travel practices. In this context, wellness tourism has emerged as a rapidly growing segment, attracting tourists seeking physical, mental, and emotional rejuvenation. This study aims to provide a comprehensive overview of wellness tourism in the post-pandemic era through a systematic literature review using the PRISMA framework. A total of 5,577 records were initially identified from major academic databases, including Scopus, ScienceDirect, and Emerald. After applying inclusion and exclusion criteria, 74 relevant studies were selected for detailed analysis. The findings reveal several key themes shaping wellness tourism research, including health recovery, post-pandemic travel behavior, technology adoption, sustainable tourism practices, destination preferences, economic impact, and industry challenges. The results indicate that tourists are increasingly prioritizing safety, hygiene, and holistic well-being, leading to a growing demand for nature-based, less crowded, and wellness-oriented destinations. Additionally, technological advancements such as digital platforms and contactless services have enhanced tourist experiences, while sustainability practices have become integral to tourism development. Despite its rapid growth, wellness tourism faces challenges such as high costs, limited accessibility, and lack of standardization. This study contributes to the existing literature by offering a structured synthesis of current research and identifying critical gaps, particularly in the integration of technology, sustainability, and cross-cultural perspectives. The findings provide valuable insights for researchers, policymakers, and industry practitioners to develop effective strategies for the sustainable growth of wellness tourism in the post-pandemic era.